1999
DOI: 10.1080/00050069908257434
|View full text |Cite
|
Sign up to set email alerts
|

Turning points in the lives of midlife and older women

Abstract: he study explored the turning points in their lives reported by 60 married or previously married lower-T income midlife and older women (born 1931-1936, 1941-1 946 and 1951-1 956), and considered the importance of age and cohort effects. Following a life-review interview, respondents were asked to nominate the turning points in their lives. The turning points that were identified were classified as involving predominantly a role transition, an adversity, or an experience of personal growth.There were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Turning points researchers recognize this by asking people to reflect on their lives and name major occurrences that have changed the course of their lives (Leonard & Burns, 1999;Ronka et al, 2003). These researchers have found that some events recognized as important in life events or transitions research were not named as turning points, even though they had occurred in that person's life.…”
Section: Transitionsmentioning
confidence: 98%
“…Turning points researchers recognize this by asking people to reflect on their lives and name major occurrences that have changed the course of their lives (Leonard & Burns, 1999;Ronka et al, 2003). These researchers have found that some events recognized as important in life events or transitions research were not named as turning points, even though they had occurred in that person's life.…”
Section: Transitionsmentioning
confidence: 98%
“…The Coming of Age longitudinal study follows the lives of three groups of women, first interviewed in their early 40s, 50s and 60s. This paper presents a comparison of the turning points identified in the first 5-year follow-up with those in the original interviews (Leonard & Burns, 1999).…”
mentioning
confidence: 99%
“…Stage 1 of the research (Leonard & Burns, 1999) showed that there were significant group differences in that the youngest cohort nominated significantly more adversities and the oldest cohort correspondingly fewer. In the total sample, role transitions and adversity turning points were most commonly experienced between the ages of 21 and 40 years, while personal development experiences increased after midlife.…”
mentioning
confidence: 99%
“…Gerontologists hold conflicting opinions about the capacities, competencies, and potentials of older people (for some divergent viewpoints see P. Baltes et al, 1996;Berg, 1996;George & Clipp, 1991;Giambra, Camp, & Grodsky, 1992;Hultsch, Hertzog, Small, & Dixon, 1999;Leonard & Burns, 1999;Rapkin & Fischer, 1992;Ryff & Keyes, 1995). One possible reason for this lack of consensus is a historical over-emphasis on studying individuals in isolation rather than as active agents interacting with their social context (P. Baltes et al, 1996;Bronfenbrenner, 1989;Labouvie-Vief & Chandler, 1978;Ranzijn, in press;Thomas & Chambers, 1989;Verhaegen, Geraerts, & Marcoen, 2000).…”
Section: Positive Psychology Can Help To Improve the Person-environmementioning
confidence: 99%